If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1(-3 + -7x) + -2(5x + 3) = 36 8 + (-3 * -1 + -7x * -1) + -2(5x + 3) = 36 8 + (3 + 7x) + -2(5x + 3) = 36 Reorder the terms: 8 + 3 + 7x + -2(3 + 5x) = 36 8 + 3 + 7x + (3 * -2 + 5x * -2) = 36 8 + 3 + 7x + (-6 + -10x) = 36 Reorder the terms: 8 + 3 + -6 + 7x + -10x = 36 Combine like terms: 8 + 3 = 11 11 + -6 + 7x + -10x = 36 Combine like terms: 11 + -6 = 5 5 + 7x + -10x = 36 Combine like terms: 7x + -10x = -3x 5 + -3x = 36 Solving 5 + -3x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 36 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 36 + -5 -3x = 36 + -5 Combine like terms: 36 + -5 = 31 -3x = 31 Divide each side by '-3'. x = -10.33333333 Simplifying x = -10.33333333
| n^2+2n-19=5 | | fx+1=9x+4 | | 10(10+8k)= | | 0.6768%= | | f(x+1)=9x+4 | | x^2+-2x+-4=0 | | -6(2n-7)+2(n+4)=-36 | | x-2x-4=0 | | 20(x-0.5)=70 | | 26-18=2(x-2) | | 540-8P=120+6P | | 4(8a+-8)= | | 8z=12 | | 2x-sin(0.5x)=0 | | 7x-12=15-4x | | 8x-(x-4)=7x | | =6P+540 | | y^2-2y-35= | | 4t-2= | | x+18+4x=-10-4x-17 | | t^2-8t=19 | | 58=-8(8m+5)-3-m+8 | | -7x+3y=38 | | 2x-(x+2)=-4 | | 19-x=14 | | 2(4-7)= | | 9t-6t+t-2= | | -109+x=34+12x | | -6-13=5x+18-4x | | 78=3(x)+18 | | 12c-15=11 | | 13*2+3= |